The impact of a hypothetical leader’s dark triad traits in the assessment of transformational leadership - Stelmokienė, Aurelija; Vadvilavičius, Tadas (Psichologija, 2019)
For quite a long period of time, transformational leadership was related only to positive antecedents and outcomes (van Knippenberg & Sitkin, 2013). However, nowadays researchers are more invited to study the “dark side” of transformational leadership (Eisenbeiß & Boerner, 2013; Vreja, Balan, & Bosca, 2016). The model of dark triad traits (Paulhus & Williams, 2002) could be an interesting topic in this contemporary discussion. Therefore, a quasi experiment was conducted with the aim to analyze the impact of a hypothetical leader’s dark triad traits in assessing transformational leadership. A total of 157 respondents (31 male and 126 females) participated in the quasi experiment. The average age of respondents was 24.87 (SD = 5.4) years, with the average of 4.5 (SD = 5.03) years of working experience. Most of the respondents (62.4%) had higher education. Respondents were asked to fill in the questionnaire about their dark triad traits (SD3, Jones & Paulhus, 2014), to read one of four scenarios (2 x 2 experiment design: male or female leader; a high or low expression of a leader’s dark triad traits) and to evaluate the transformational leadership of a hypothetical leader in the scenario (GTL scale, Carless, Wearing, & Mann, 2000). The analysis revealed that the index of transformational leadership was higher when hypothetical leaders with a low expression of dark triad traits were assessed in comparison with hypothetical leaders who possessed a high expression of dark triad traits. So, the main hypothesis was confirmed. However, an additional analysis of the factors that could be also important in predicting the assessment of transformational leadership did not support the significant role of the assessor’s or the assessee’s gender or the assessing individual’s dark triad traits. Nevertheless, contextual factors in the assessment of transformational leadership deserve further attention from researchers and practitioners. In general, the impact of a hypothetical leader’s dark triad traits in the assessment of transformational leadership is significant: the higher expression of dark triad traits, the less transformational leadership. With reference to scientific literature (Hoch, Bommer, Dulebohn, & Wu, 2018; Brymer & Gray, 2006; Jung, Chow, & Wu, 2003), transformational leadership is set as a criteria of effective leadership. Therefore, if practitioners wish to have an effective leader whom subordinates are ready to follow in their organizations, they should pay attention to how these subordinates evaluate their leaders’ dark triad traits. However, these results need confirmation in a field survey.